2018
DOI: 10.18517/ijaseit.8.2.4087
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Egg White Powder from Eggs of Different Types of Bird

Abstract: The objective of this study was to compare the physicochemical properties of egg white powder from eggs of different types of bird (local kampung chicken, local fighting chicken, local serama chicken, leghorn chicken, turkey, and guineafowl). Eggs were purchased from local farmers. Egg whites were separated from egg yolks manually, blast frozen, freeze-dried, and ground into powder. Moisture and protein content, colour, emulsification activity and stability, foaming capacity and stability, water holding capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Egg white flour using BTP CMC has a higher L value than control and maltodextrin use, this value is almost the same as commercial egg white flour. The brightness value of egg white flour ranges from 93.91 -95.11, this value is better than the brightness value of egg white flour from the research results Kai Sze et al (2018) [16] between 91-92%. During drying there is a change in the color of the egg flour which is a Maillard reaction.…”
Section: Proximate Assaysmentioning
confidence: 63%
“…Egg white flour using BTP CMC has a higher L value than control and maltodextrin use, this value is almost the same as commercial egg white flour. The brightness value of egg white flour ranges from 93.91 -95.11, this value is better than the brightness value of egg white flour from the research results Kai Sze et al (2018) [16] between 91-92%. During drying there is a change in the color of the egg flour which is a Maillard reaction.…”
Section: Proximate Assaysmentioning
confidence: 63%
“…The ability of a protein to bind water is affected by many factors, including pH and ionic strength [30]. [31] showed that the ability to bind water is an important factor in the formation of protein gels. The physical and chemical properties of egg white powder from different types of poultry birds were studied in terms of the ability of egg white powder to bind water.…”
Section: Water Winding Capacitymentioning
confidence: 99%
“…The volume of the foam and volume of the egg white solution were measured after 30 min. The foaming ability and stability were calculated using the formula below (Sze et al, 2018):…”
Section: Functional Properties Analyses Foaming Abilitymentioning
confidence: 99%
“…Thus, colour plays an important role in evaluating food quality. Based on the Hunter Lab colour scale system, L* indicates brightness (whiteness (+) or darkness (-)), a* indicates redness (+) or greenness (-), b* indicates yellowness (+) or blueness (-), and delta value (ΔE) shows the differences between standard and each sample in terms of L*, a*and b* (Sze et al, 2018).…”
Section: Colour Analysismentioning
confidence: 99%